Impacto de las ferias vocacionales en la orientación vocacional - Olivares P., Margarita (2013)
The present investigation is to determine the impact of vocational fairs in vocational guidance. The sample consisted of 215 female students, enrolled in the 5th grade of secondary and high school graduates, aged 15 to 25 years, from state and private schools of Lima. The instrument used was one multiple-choice questionnaire. The results were: The group of students assessed, states that 82. 8% have a decision on the career they want to study and 17.5% not have such a decision. The sources of information in order of importance they have used to take their career decision are: the Internet, specialized books and newspapers, magazines and vocational fairs. The criteria used in hierarchical order, in the decision making of the profession are “the most liked profession”, “the prestige of the profession” and “the recommendation of family and / or friends.” In relation to the level of assistance provided by vocational fairs for decision making, 57.2% consider vocational fairs contributed little in his decision, while 36.7% think that were marked importance in their career choices. Regarding the degree of importance they attach to the components presented in vocational fairs, the students give more importance to the oral explanation (71.6%), while 20.9% were interested in the written information. Finally in relation to the possibility to consider the advisability of continuing vocational fairs, we found that 91% believe in favor of continuing to make these events. The impact of the vocational fairs in the vocational orientation is partial.